Deficient supplementary motor area at rest: Neural basis of limb kinetic deficits in Parkinson's disease. Issue 9 (2nd May 2018) - Kübel, Stefanie; Stegmayer, Katharina; Vanbellingen, Tim; Walther, Sebastian; Bohlhalter, Stephan
Abstract: Parkinson's disease (PD) patients frequently suffer from limb kinetic apraxia (LKA) affecting quality of life. LKA denotes an impairment of precise and independent finger movements beyond bradykinesia, which is reliably assessed by coin rotation (CR) task. BOLD fMRI detected activation of a left inferior parietal‐premotor praxis network in PD during CR. Here, we explored which network site is most critical for LKA using arterial spin labeling (ASL). Based on a hierarchical model, we hypothesized that LKA would predominantly affect the functional integrity of premotor areas including supplementary motor areas (SMA). Furthermore, we suspected that for praxis function with higher demand on temporal‐spatial processing such as gesturing, inferior parietal lobule (IPL) upstream to premotor areas would be essential. A total of 21 PD patients and 20 healthy controls underwent ASL acquisition during rest. Behavioral assessment outside the scanner involved the CR, finger tapping task, and the test of upper limb apraxia (TULIA). Whole‐brain analysis of activity at rest showed a significant reduction of CR‐related perfusion in the left SMA of PD. Furthermore, the positive correlation between SMA perfusion and CR, seen in controls, was lost in patients. By contrast, TULIA was significantly associated with the perfusion of left IPL in both patients and controls. In conclusion, the findings suggest that LKA in PD are linked to an intrinsic disruption of the left SMA function, which may only be overcome by compensatory network activation. In addition, gestural performance relies on IPL which remains available for functional recruitment in early PD.